Tārīqah Taqdim al-Qissah Fī Tarqiyah Mahārah al-Istimā’ Litullāb al-Mustawā al-Sānī al-Mukaṡṡaf Bijāmi’ah al-Amīn al-Islāmiyyah Prenduan Sumenep Madura - Sulton, Moh.; ., Shobirin (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2020)
Abstrack If you look at each of the four language skills, it will be clear that the first is listening skill, because good listening is a basic factor in being able to master the other three skills, then the story presentation method becomes a teaching method based on presenting information and facts are anecdotal, and have a good effect on attracting the listener's attention. The purpose of this scientific research is to find out whether the storytelling method able to affect the increase in the listening ability of students for Intensive Program of the Dirosat Islamiyah Al-Amien Prenduan, and the extent of its impact. This scientific research is quantitative in nature, by taking data from students for the intensive program of the Dirosat Islamiyah Al-Amien Prenduan, and the total sample of 20 people. The data collection technique was used by using questionnaires which aimed to test the independent and the dependent variables. Observation and documents to confirm and verify, while for the data analysis method the data analysis method is the product moment correlation method, from the results of data analysis it is clear that the storytelling method affects in improving the student’s listening skills of intensive programe of Institut Dirosat Islamiyah Al-Amien Prenduan. Keywords: Influence, Storytelling Methods, Listening Skill